Positive and Negative Excesses of Online Games among Muslim Adolescents in Tanah Datar, West Sumatra - Nora, Vivi Yulia (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This study aims to determine the factors and impact of online games on the behavior of Muslim adolescents in Jorong Tabek, Tanah Datar District, West Sumatra. The field methods used in this qualitative research were observation, interviews, focus group discussions, and the informants' documentation, which were determined by purposive sampling. The theoretical perspective of this research uses structural-functional and hipper-reality. The results of this study indicate that online games have negative and positive impacts on Muslim adolescents. For informants, online games have a positive impact because they are a medium of entertainment, relieve boredom, spend time, enrich friendships, and help them increase their English vocabulary. On the other hand, the informants also admitted that online games impacted negligence in performing prayers and other religious activities such as wirid and tadarus during Ramadan, negligence to studying, forgetting to eat, ignoring parents' words, and saying harsh words up to physical violence. The triggering factors that caused the informants to choose to play online games were boredom, lack of facilities and infrastructure to channel their hobbies, and the fact that the online game was currentlyÂ viral.